Development, Validation, and Performance Evaluation of An Air-Driven Free-Piston Linear Expander Numerical Model - Raheem, A.T. (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2022)
The free piston linear expander (FPLE) is an energy conversion device that converts mechanical energy into electric energy by using a linear electric machine (LEM) without emission. This research addresses the numerical modeling of a dual-piston air-driven FPLE constructed on the basis of the free piston engine linear generator (FPELG) concept. The model was built in MATLAB/Simulink. The simulation results were in good agreement with the experimental data. Where the in-cylinder pressure and displacement profiles attained errors of less than 10 (within the acceptable range). Then, the predicted results of the simulation model, namely, the displacement profile, in-cylinder pressure, piston velocity, and engine power results were analyzed. Findings indicate that intake pressure was the most important parameter for enhancing engine performance. The in-cylinder pressure increased by approximately 16 and 21.7 when the intake pressure was increased from 5 to 6 bar and from 6 to 7 bar, respectively. The piston velocity increased by approximately 12.3 when the intake pressure increased by 1 bar. Finally, engine power increased by approximately 26.5 and 30.6 when the intake pressure increased from 5 to 6 bar and from 6 to 7 bar, respectively. Â© 2022 Novel Carbon Resource Sciences. All rights reserved.